2016
DOI: 10.1111/evo.12894
|View full text |Cite
|
Sign up to set email alerts
|

Tightly congruent bursts of lineage and phenotypic diversification identified in a continental ant radiation

Abstract: Adaptive diversification is thought to be shaped by ecological opportunity. A prediction of this ecological process of diversification is that it should result in congruent bursts of lineage and phenotypic diversification, but few studies have found this expected association. Here, we study the relationship between rates of lineage diversification and body size evolution in the turtle ants, a diverse Neotropical clade. Using a near complete, time-calibrated phylogeny we investigated lineage diversification dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 67 publications
2
70
0
Order By: Relevance
“…; Price et al. ). However, to date, relatively little work has integrated phylogenetic and eco‐morphogical data to address trait‐based diversification and evolutionary processes in ants, especially on a broad, family‐wide scale.…”
mentioning
confidence: 97%
“…; Price et al. ). However, to date, relatively little work has integrated phylogenetic and eco‐morphogical data to address trait‐based diversification and evolutionary processes in ants, especially on a broad, family‐wide scale.…”
mentioning
confidence: 97%
“…; Price et al. ; Puttick ), they are far from common and an analysis of 44 extant clades, including some of the most iconic examples of adaptive radiation, revealed a dearth of support for early‐burst dynamics in both size and shape data (Harmon et al. ).…”
mentioning
confidence: 99%
“…Alternatively, rates of speciation and phenotypic evolution can be decoupled in "cryptic" species complexes or nonadaptive radiations (Gittenberger 1991;Kozak et al 2006;Rundell and Price 2009). Previous macroevolutionary studies have found that rates of phenotypic evolution and speciation are correlated in some clades or traits (Rabosky and Adams 2012;Rabosky et al 2013;Puttick et al 2015;Price et al 2016;Ramírez-Barahona et al 2016) and uncorrelated in others (Adams et al 2009;Venditti et al 2012;Burbrink et al 2012;Bapst et al 2012;Zelditch et al 2015;Lee et al 2016), suggesting that both of these patterns may be widespread in nature.…”
mentioning
confidence: 99%